Solid waste management in Asian countries: a review of solid waste minimisation (3 ' r) towards low carbon - Ali, Norizan (Institute of Physics Publishing, 2014)
The amount of solid-waste generated in Asian countries has increased tremendously, mainly due to the improvement in living standards, rapid developments in technology, growth in economy and population in the cities. Solid waste management is a global issue and major challenge facing Asian countries and neglecting its management may have negative consequences on the environment. Waste composition data proves the developed countries to have generated more recyclable materials while developing countries produce more organic and less recyclable waste such as paper, plastic and aluminium. In this regard, increase in number of landfills and disposal sites, will have an impact on GHG (greenhouse gas) emissions and pollutants to air and water. Alternative methods should therefore be taken to reduce the volume of waste. Most Asian countries have adopted the 3R (reduce, reuse, recycle) concept in order to reduce solid waste and their governments have implemented laws and regulations in order to support this. Implementation of 3R is the major contributor to the solid waste minimization and it can improve the quality of environmental sustainability and reduction of carbon dioxide emission in to the atmosphere. Based on our review, most of the countries practicing the 3R concept in tandem with laws and regulations perform better than those that just practice the 3R concept without any laws and regulations. The paper suggests that every country must focus on the laws and regulations relating to solid waste minimization so that it could be easily implemented as outlined.